A Comparison of Catchability and Mortality with Circle and J Hooks for Stream-Dwelling Brook Trout. (3rd March 2016) - Kazyak, David C.; Sell, Matthew T.; Hilderbrand, Robert H.; Heft, Alan A.; Cooper, Ryan M.
Abstract: We compared the effectiveness of baited circle hooks and J hooks in catch-and-release angling for wild, stream-dwelling Brook Trout Salvelinus fontinalis . We caught 201 Brook Trout using active and passive techniques to assess the influence of hook type and angling method on capture efficiency, hooking location, handling time, deep-hooking rates, and postrelease mortality (up to 48 h). Anglers recorded an average catch rate of 7.6 trout/h over 26.25 total hours of fishing. Actively fishing with J hooks was the most effective at landing Brook Trout (82.3%). Only 10% ( n = 20) of all fish were deeply hooked, and half of those were caught when anglers were passively fishing with J hooks. Larger fish were significantly more likely to be deeply hooked. However, no fish were deeply hooked when anglers passively fished with circle hooks. The most common hooking location among treatments was the corner of the mouth (40%, n = 80). Eye injuries due to hooking were relatively uncommon (6.5%) and occurred less frequently than deep hooking. Overall mortality rates were very low (2%, n = 4) and were probably influenced by low deep-hooking rates in concert with cool water temperatures and experienced anglers equipped with the necessary tools to efficiently release the trout. Received May 19, 2015; accepted November 12, 2015 Published online March 16, 2016